Resistance, virulence and genetic relatedness of invasive Staphylococcus aureus isolates collected from private and public clinical settings in South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2023)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2022.